Desenvolvimento territorial e sustentabilidade no alto Camaquã: um estudo de caso no Município de Lavras do Sul-RS - Silva, Cristiane de Farias Betemps da (2012)
This study aimed to analyze socio-productive strategies in the Upper Camaquã area so as to understand the relations between sustainability and territorial development. For such, it sought at first to characterize what the socio-productive activities in the researched county actually were, including both traditional and innovative ones. From this, a relation between sustainable and territorial development, for the purpose of understanding the generation of new socio-productive strategies within the territory, was established. The study also performed an investigation to identify the developmental perception from a territorial approach, which demystified the use of the analytical categories backward or poor in the researched territory. This analysis was based on new practices in the use of natural and human resources (local culture), production diversity (ecosystem potentials) and decision and demand decentralization in the territory ( development coordination, planning and management by agencies at different levels). The study also pointed to territorial development prospects for Lavras do Sul, as evidenced in the economic, cultural and political dimensions of the territory. Thus, socio-productive strategies are relevant for the appreciation of the area, bearing in mind the ecological, social, cultural, economic and political sustainability. However, only changes in the local culture can lead to deep socio -economic and political-institutional territory transformations, i. e. the actions of social agents as the main characters in the building of new territories is key for the eradication of the backward and poor misconceptions in the rural areas. The constructive partnership concept of human society, with the proper use of local power in decision-making, will guide the wanted kind of development for Lavras do Sul County